Managerial Decision Making With The Role Of Management Information Systems (MIS): What The Literature Says - Sari, Ery Novita; Priantinah, Denis (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2019)
The management information system used in the organization has now increased when seen from its efficiency and effectiveness. The initial stage of developing management information systems aims to improve the efficiency of activities in the organization. So that it is considered as part of a comprehensive organizational strategy. An important focus of MIS is on data collection. Because organizations are said to be successful if the quality of data collection is high. Management information systems also aim at decision making in an organization. The overall review of the literature highlights that management information systems play a major role in decision making in an organization. So the expected results of the study explain specifically the role of management information system in managerial decision making.